Geotechnical finite element analysis a practical guide - Lees, Andrew (ICE Publishing, 2016)
Geotechnical Finite Element Analysis provides the latest practical guidance and comprehensive explanations of applying finite element analysis (FEA) in geotechnical design - from planning and analysis, determining how the FEA relates to the design process and explaining the decisions that need to be made at each stage through to validation of results and reporting.